BAHASA DAN REALITAS: SUATU PENDEKATAN PSIKOLOGISME - Fauzi, Mohd.; Hutahaean, Sorta (Universitas Lancang Kuning, 2014)
Psychologism is one of the important fields in linguistics which proposes that language does not only deal with the process of interaction but it is also considered a mental process upon which spoken or written language depends. This field is closely related to psycholinguistics. To have ability in interaction, human beings need to understand language elements, such as the form, the function and the meaning. Utterances in any language produced by someone undergoes mental process. It means that the production of every single word is an embodiment of mental and thought. Accordingly, the language produced by someone reflects an embodiment of his/her world.